Sand minimum transport conditions in gas–solid–liquid three-phase stratified flow in a horizontal pipe at low particle concentrations - Fajemidupe, Olawale T.; Aliyu, Aliyu M.; Baba, Yahaya D.; Archibong-Eso, Archibong; Yeung, Hoi (Elsevier, 2019)
Sand production in the life of oil and gas reservoirs is inevitable, as it is co-produced from reservoirs. Its deposition in petroleum pipelines poses considerable risk to production and can lead to pipe corrosion and flow assurance challenges. Therefore, it is important that pipe flow conditions are maintained to ensure sand particles are not deposited but in continuous motion with the flow. The combination of minimum gas and liquid velocities that ensure continuous sand motion is known as the minimum transport condition (MTC). This study investigates the effect both of sand particle diameter and concentration on MTC in gas/liquid stratified flow in a horizontal pipeline. We used non-intrusive conductivity sensors for sand detection. These sensors, used for film thickness measurement in gas/liquid flows, were used for the first time here for sand detection. We found that MTC increases with increase in particle diameter for the same concentration and also increases as the concentration increases for the same particle diameter. A correlation is proposed for the prediction of sand transport at MTC in air–water flows in horizontal pipes, by including the effect of sand concentration in Thomas’s lower model. The correlation accounts for low sand concentrations and gave excellent predictions when compared with the experimental results at MTC.
Keywords: Sand transport; Pressure gradient; Conductivity probes; Stratified flow; Minimum transport conditions; Multiphase flow